Crystal structures of functional building blocks derived from bis(benzo[b]thiophen‐2‐yl)methane. Issue 9 (26th August 2016) - Katzsch, Felix; Gruber, Tobias; Weber, Edwin
Abstract : The syntheses of three bis(benzo[ b ]thiophen‐2‐yl)methane derivatives are described and their crystal structures discussed comparatively. The conformations of the title compounds are compared with respective bioisoteres and active pharmaceutical ingredients (APIs) containing the dithiophen‐2‐ylmethane scaffold. Abstract : The syntheses of three bis(benzo[ b ]thiophen‐2‐yl)methane derivatives, namely bis(benzo[ b ]thiophen‐2‐yl)methanone, C17 H10 OS2, (I), 1, 1‐bis(benzo[ b ]thiophen‐2‐yl)‐3‐(trimethylsilyl)prop‐2‐yn‐1‐ol, C22 H20 OS2 Si, (II), and 1, 1‐bis(benzo[ b ]thiophen‐2‐yl)prop‐2‐yn‐1‐ol, C19 H12 OS2, (III), are described and their crystal structures discussed comparatively. The conformation of ketone (I) and the respective analogues are rather similar for most of the compounds compared. This is true for the interplanar angles, the Caryl —Cbridge —Caryl angles and the dihedral angles. The best resemblance is found for a bioisotere of (I), viz. 2, 2′‐dinaphthyl ketone, (VII). By way of interest, the crystal packings also reveal similarities between (I) and (VII). In (I), the edge‐to‐face interactions seen between two napthyl residues in (VII) are substituted by S…π contacts between the benzo[ b ]thiophen‐2‐yl units in (I). In the structures of the bis(benzo[ b ]thiophen‐2‐yl)methanols, i.e. (II) and (III), the interplanar angles are also quite similar compared with analogues and related active pharmaceutical ingredients (APIs) containing the dithiophen‐2‐ylmethane scaffold, though the dihedral angles show a larger variability and produce unsymmetrical molecules.